INNOVATIVE APPROACHES TO FOREIGN LANGUAGE PEDAGOGY IN VIRTUAL LEARNING ENVIRONMENTS USING SOCIAL MEDIA: CHALLENGES AND OPPORTUNITIES: INNOVATIVE APPROACHES TO FOREIGN LANGUAGE PEDAGOGY IN VIRTUAL LEARNING ENVIRONMENTS USING SOCIAL MEDIA: CHALLENGES AND OPPORTUNITIES - Dilmanov, Ilya (Журнал иностранных языков и лингвистики, 2025)
Virtual learning environments have revolutionized how languages are taught and learned. Platforms such as Zoom facilitate real-time interaction, while Google Classroom provides a structured space for assignments and resources. Telegram offers a more informal setting for communication and collaboration. Together, these tools create a multifaceted learning experience that can enhance language acquisition.